2016
DOI: 10.1007/s11255-016-1425-6
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB expression and its association with nutritional status in hemodialysis patients

Abstract: The classical NF-κB activation seems to be associated with poor nutritional status in HD patients; however, the exact underlying mechanisms deserve further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Activation of NFkB via the UPS and the MuRF1 pathways induces muscle degradation and muscle wasting, which in turn induces cellular apoptosis [19]. Higher levels of NFkB have been observed in hemodialysis patients with poor nutritional status, reinforcing the hypothesis that inflammation is a key driver of PEW [34]. Furthermore, blocking the translocation to the nucleus by pharmacological or genetic inhibition of NFkB prevents the expression of several components of the proteolytic machinery including MuRF1, muscle synthesis and preservation [6].…”
Section: Ubiquitin-proteasome System: Nrf2 Signaling Pathway and Its ...mentioning
confidence: 97%
See 1 more Smart Citation
“…Activation of NFkB via the UPS and the MuRF1 pathways induces muscle degradation and muscle wasting, which in turn induces cellular apoptosis [19]. Higher levels of NFkB have been observed in hemodialysis patients with poor nutritional status, reinforcing the hypothesis that inflammation is a key driver of PEW [34]. Furthermore, blocking the translocation to the nucleus by pharmacological or genetic inhibition of NFkB prevents the expression of several components of the proteolytic machinery including MuRF1, muscle synthesis and preservation [6].…”
Section: Ubiquitin-proteasome System: Nrf2 Signaling Pathway and Its ...mentioning
confidence: 97%
“…NRF2 deficiency may exacerbate age-related mitochondrial oxidative stress in aged skeletal muscle [ 46 ] and be part of an intermediate inflammatory phenotype that promotes burden of lifestyle diseases that accumulate with age [ 47 ]. The decrease in the number of fat-free myocytes and the low transcription of NRF2 [ 44 ] may be related to several factors, such as inadequate diet, hyperparathyroidism, depression, dementia, osteoporosis, periodontitis [ 43 ], dialysis, uremic toxins [ 48 ], obesity, hyperglycemia, variants of NFE2L2 gene (encoding NRF2 protein) [ 22 , 49 ], metabolic acidosis and endothelial dysfunction [ 23 , 34 ]. All these factors promote muscle degradation and may contribute to skeletal muscle dysfunction by inducing ubiquitination, lipid peroxidation and activation of apoptotic processes and autophagy with mediators such as calpain and caspases [ 18 ].…”
Section: Ubiquitin–proteasome System: Nrf2 Signaling Pathway and Its ...mentioning
confidence: 99%
“…Eleven studies were eligible. One study investigated NRF2 in HD patients and found no correlation to biochemical and anthropometrical parameters [68].…”
Section: Relation Between Nrf2 Nqo1 and Ho-1 And Clinically Relevant ...mentioning
confidence: 99%